DNA of the young entrepreneur [electronic resource] : a way to wealth for young entrepreneurs - McCauley, Sean (HappyAboutinfo, 2008)
A compelling mixture of philosophy, personal experience, and practical advice. The book takes the reader on a journey through knowledge, attitudes, values, and actions that spell the difference between success and failure in starting and running a small